The Role of Social Media in Forming Public Opinion about Islamophobia in Indonesia - Budiawan, Budiawan; Cindrakasih, Roosita; Puspitaningrum, Deby; Fajar, Adityo; Kurniawan, Fajar (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Islamophobia, a growing concern worldwide, has been increasingly shaped by the spread of misinformation and negative stereotypes through social media platforms. In Indonesia, where Islam is the predominant religion, the rise of Islamophobic discourse on social media has created significant challenges for the Muslim community and interfaith relations. This study explores the role of social media in shaping public opinion about Islamophobia in Indonesia. The research investigates how social media platforms, particularly Twitter, Facebook, and Instagram, contribute to the formation and dissemination of Islamophobic narratives, and how these narratives influence public perceptions of Islam and Muslims. A mixed-methods approach was used, combining content analysis of social media posts with surveys of Indonesian internet users to assess their awareness of Islamophobic content and its effects. The findings reveal that social media platforms play a critical role in amplifying Islamophobic discourse, often without sufficient counter-narratives or fact-checking. The study concludes that social media has a dual role, both as a platform for disseminating negative stereotypes and as a potential space for countering Islamophobia through education and positive engagement.